Recent Legal Developments: Criminal Justice Decisions of the United States Supreme Court, 2,020 Term - Hemmens, Craig (Criminal justice review, 2022)
In this paper we review and analyze the criminal justice-related decisions of the 2,020 term of the United States Supreme Court. We also provide a summary of the Court’s voting patterns and opinion authorship. Thirteen of the Court’s 57 decisions touched on criminal justice. There were significant decisions involving the Fourth Amendment, the Eighth Amendment, and federal criminal statutes. Each of these is discussed in turn.